Metodología de la enseñanza y aprendizaje del idioma inglés mediante el uso del vocabulario en los estudiantes del segundo año de bachillerato general unificado de la Unidad Educativa San Pablo de Atenas durante el año lectivo 2015-2016 - Pazmiño Del Pozo, Darwin Marcelino (2016)
In this methodological proposal are established methodological theoretical bases for teaching and learning the foreign language “English” by applying educational activities as the use of vocabulary implemented in second year students General Unified Baccalaureate Education Unit “San Pablo de Atenas”. Therefore is it necessary to apply and enforce the teaching of a second language by English teachers in the area and to wake the interest of students to learn basic knowledge on the subject of foreign language an efficient way. Because it is a pedagogical activity that begins as a proposal to improve teaching and learning of language "English" for the purpose of create an alternative that favor the process of applying methods, techniques and strategies for teaching English by teachers and students of the institution. It took into account action research to strengthen educational practice where it is could get an information gathering qualitative and quantitative data to analyze, describe, interpret and explain through information techniques such as observation and survey where it was verified that the methodology implemented by the teacher in the classroom and the manifestation of students to acquire basic knowledge of the foreign language through a new methodology are developed educational activities such as the use of vocabulary different topics with a translation into Spanish so achieve that students have a better learning and increase their knowledge on the subject of Foreign Language. With this proposal is expected to improve the teaching and learning of English in Education Unit “San Pablo de Atenas” implementing this methodology and pedagogical model where students develop fundamental skills in a foreign language "English" because the same students listening, speaking, reading and writing, allowing them to enrich their knowledge and improve their academic level besides this methodology classes are more dynamic and attractive that attract attention and interest of students to learn the language.